A giant and rapid myocardial remodeling due to fatal giant cell myocarditis: a case report - Zhang, Wei; Guo, Tao (Frontiers in Cardiovascular Medicine, 2025)
Giant cell myocarditis is a rare and rapidly progressive disease with a high mortality rate. We present the case of a 21-year-old male without a medical history who presented with a giant left ventricle (9.9 cm, EF:10%) and in a severe clinical state. Cardiac MRI and virology raised the suspicion of giant cell myocarditis. Concerned about the hemodynamic and respiratory deterioration, we initiated cardiac transplant therapy. A fatal ventricular fibrillation occurs while waiting for the heart transplant. Sudden death could represent the “first symptom” of pathological findings. It is important to recognize that while sudden death due to giant cell myocarditis may be rare, it is still a potentially serious complication of giant cell infection and should be considered in cases of unexplained sudden death. In addition, this case highlights the challenges in the diagnosis and management of giant cell myocarditis and the need for early recognition and aggressive treatment.